Review of National Sport effort & resources - Carter, P. (2005)
Commonly known as the Carter report - Sir Patrick Carter [Lord Carter of Coles] was the Chair of Sport England in 2005, this report was written just prior to the awarding of the Olympic Games - 2012 to London and it was addressed from Sport England to the Government. In it Lord Carter says;